The liberation revolution in the second zone of the third region of the fourth wilaya 1957-1962 - belalia, Miloud (The Algerian Historical Journal, 2026)
This article aims to highlight the activity of the liberation revolution in the second part of the third region of the fourth term (1957-1962) and to mobilize the algerian people to secure support for the National Liberation Army despite the dependence of france's policy on its agents to isolate the people from their revolution. In the summer of 1957, the mujahideen succeeded in contacting the residents of the Kefafsa roundabout to form the first revolutionary cell and mobilize them to secure the operations of the National Liberation Army and boycott compulsory self-defense service in the guard post of the roundabout established by the enemy in 1958.One of the results of this research paper is that the FLN succeeded in achieving the objectives of the november first statement in aborting france's policy of isolating the people from the revolution, as evidenced by the martyrs, the mujahideen, the muslims and those sentenced to death in this roundabout, especially the elimination of france's agent Bouchakor in august 1961 until independence in 1962.